2019
DOI: 10.1186/s12906-019-2745-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a mouthrinse containing guava leaf extract as part of comprehensive oral care regimen- a randomized placebo-controlled clinical trial

Abstract: Background: The control of biofilm adherence on tooth surface has always been the keystone of periodontal therapeutic systems. However, prevalence of gingivitis suggest inadequacy of self-performed oral hygiene measures and need for adjunctive aid for mechanical plaque control. Oral rinses containing chlorhexidine, has been widely used however, with certain limitations. Herbal products have been used widely reflecting its action as alternative and complementary remedy. Hence, the purpose of the present study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
1
18
0
3
Order By: Relevance
“…However the difference in plaque and gingival index scores between the group using aloe vera, tea tree oil and chlorhexidine, was not statistically significant. Whereas study on guava mouthwash showed that mean plaque index and gingival index scores from baseline to 30 days had notable changes between chlorhexidine and guava mouth rinse compared to placebo [ 47 ]. In 14 studies, 4 studies assessed the total microbial count on administration of antioxidant mouthwashes, one study specifically evaluated the streptococcus mutans level at the baseline and postoperatively, all the 4 studies showed that the microbial counts where reduced on the usage of antioxidant mouth compared to the baseline value, however they had similar microbiological effect has that of the chlorhexidine mouthwash [ 33 , 44 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However the difference in plaque and gingival index scores between the group using aloe vera, tea tree oil and chlorhexidine, was not statistically significant. Whereas study on guava mouthwash showed that mean plaque index and gingival index scores from baseline to 30 days had notable changes between chlorhexidine and guava mouth rinse compared to placebo [ 47 ]. In 14 studies, 4 studies assessed the total microbial count on administration of antioxidant mouthwashes, one study specifically evaluated the streptococcus mutans level at the baseline and postoperatively, all the 4 studies showed that the microbial counts where reduced on the usage of antioxidant mouth compared to the baseline value, however they had similar microbiological effect has that of the chlorhexidine mouthwash [ 33 , 44 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas study on guava mouthwash showed that mean plaque index and gingival index scores from baseline to 30 days had notable changes between chlorhexidine and guava mouth rinse compared to placebo [ 47 ]. In 14 studies, 4 studies assessed the total microbial count on administration of antioxidant mouthwashes, one study specifically evaluated the streptococcus mutans level at the baseline and postoperatively, all the 4 studies showed that the microbial counts where reduced on the usage of antioxidant mouth compared to the baseline value, however they had similar microbiological effect has that of the chlorhexidine mouthwash [ 33 , 44 , 46 , 47 ]. Quality assessment of 14 selected studies was carried out based on CONSORT Guidelines 4 major criteria to evaluate risk of bias: (1) Randomization, (2) Allocation concealment, (3) Assessor blinding and (4) Dropouts.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, CHX is a synthetic chemical agent, which can have many side effects following long-term application [18]. Thus, long-term use of chemical agents is not recommended [15]. In the recent years, the demand for alternative plaque removal methods has greatly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorhexidine (CHX) is the gold standard for chemical removal of microbial plaque, which is often prescribed as an adjunct to mechanical plaque removal methods. However, long-term use of chemical agents is not recommended [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the therapy using natural products is generally less expensive as compared with highly pure chemicals. Moreover, it is likely that a range of natural product-based therapies could become an alternative treatment option for periodontitis [6,7]. Curry leaf (Murraya koenigii)…”
Section: Introductionmentioning
confidence: 99%